PRODUK UNGGULAN INDUSTRI RUMAH TANGGA BERBASIS PERIKANAN LAUT DI KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Leila Ariyani Sofia (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2018)
This study aims to: (1) identify the types of home industry products based on marine fishery, and (2) to determine marine fishery products that can be developed as regional leading products. Four sub-districts of coastal areas of Tanah Laut regency were chosen purposeful as study locations, namely Kurau, Jorong, Panyipatan and Takisung. Primary data collection was conducted through survey and interview to sample of marine fishery product home industry which was taken by simple random sampling. Selection of marine fisheries home industry superior product using Analytic Hierarchy Process (AHP) technique. The result of analysis showed that the home industries in the coastal area ofTanah Laut Regency is dominated by simple technology with the products produced in the form of traditional products, such as salted fish, fish and shrimp crackers, and “amplang”crackers, dried shrimp, shrimp paste, fish floss. The leading product alternatives of marine fisheries home industries in Tanah Laut regency are determined based on the criteria of raw material availability, raw material quality, value added product, technological mastery level, market opportunity, labor absorption, and current industrial product development condition shows that cracker product selected fish as a product that can be seeded with atotal value of 0.245, the next shrimp crackers and fish/shrimp floss each with a total valueof 0.221 and 0.152.